Randomized clinical trial of a brief and extensive dyadic intervention for advanced cancer patients and their family caregivers. Issue 3 (31st January 2012) - Northouse, Laurel L.; Mood, Darlene W.; Schafenacker, Ann; Kalemkerian, Gregory; Zalupski, Mark; LoRusso, Patricia; Hayes, Daniel F.; Hussain, Maha; Ruckdeschel, John; Fendrick, A. Mark; Trask, Peter C.; Ronis, David L.; et al.
Abstract Background Few intervention programs assist patients and their family caregivers to manage advanced cancer and maintain their quality of life (QOL). This study examined (i) whether patient–caregiver dyads (i.e., pairs) randomly assigned to a brief or extensive dyadic intervention (the FOCUS Program) had better outcomes than dyads randomly assigned to usual care and (ii) whether patients' risk for distress and other factors moderated the effect of the brief or extensive program on outcomes. Methods Advanced cancer patients and their caregivers (N = 484 dyads) were stratified by patients' baseline risk for distress (high versus low), cancer type (lung, colorectal, breast, or prostate), and research site and then randomly assigned to a brief (three‐session) or extensive (six‐session) intervention or control. The interventions offered dyads information and support. Intermediary outcomes were appraisals (i.e., appraisal of illness/caregiving, uncertainty, and hopelessness) and resources (i.e., coping, interpersonal relationships, and self‐efficacy). The primary outcome was QOL. Data were collected prior to intervention and post‐intervention (3 and 6 months from baseline). The final sample was 302 dyads. Repeated measures MANCOVA was used to evaluate outcomes. Results Significant group by time interactions showed that there was an improvement in dyads' coping (p < 0.05), self‐efficacy (p < 0.05), and social QOL (p < 0.01) and in caregivers' emotional QOL (p < 0.05). Effects varied by intervention dose. Most effects were found at 3 months only. Risk for distress accounted for very few moderation effects. Conclusions Both brief and extensive programs had positive outcomes for patient–caregiver dyads, but few sustained effects. Patient–caregiver dyads benefit when viewed as the 'unit of care'. Copyright © 2012 John Wiley & Sons, Ltd.